Positioning of the Tibial Tunnel After Single-Bundle ACL Primary Reconstruction on 3D CT scans: A New Method - Paul Cremer, Ph.D; Adrien Peltier, Ph.D; Laurent Maubisson, Ph.D; Philippe Neyret, M.D., Ph.D; Sébastien Lustig, M.D., Ph.D; Elvire Servien, M.D., Ph.D (Elsevier, 2020)
Purpose: To assess intra-articular tunnel aperture positioning after primary anterior cruciate ligament (ACL) reconstruction with either the reference standard method or the intercondylar area method in a single center using 3-dimensional (3D) computed tomography (CT) scans and to evaluate the intra-articular position of the tibial tunnel relative to the ACL footprint. Methods: 3D CT scans were performed after 120 single-bundle primary ACL reconstruction cases. The center of the tibial tunnel aperture and the center of the ACL footprint were referenced on axial views of the tibial plateau in the anteroposterior (AP) and mediolateral (ML) planes according to a centimetric grid system including the whole plateau (reference standard). This was compared with a grid system based on intercondylar area bony anatomy. The posterior aspect of intertubercular fossa, anterior aspect of the tibial plateau, medial intercondylar ridge, and crossing point between lateral intercondylar ridge and posterior margin were used as landmarks to define the grid. Results: According to the reference standard method, the center of the tibial tunnel aperture was positioned 0.57 ± 2.62 mm more posterior and 0.67 ± 1.55 mm more medial than the center of the footprint. According to the intercondylar area method, the center of the tibial tunnel aperture was positioned 1.32 ± 2.74 mm more posterior and 0.66 ± 1.56 mm more medial than the center of the footprint. The position difference between the center of the tunnel aperture and the center of the footprint were statistically correlated for both grids, with r = -0.887, P < .001 for AP positioning and r = 0.615, P < .001 for ML positioning. Conclusion: This intercondylar area method using arthroscopic landmarks can be used to assess tunnel placement on 3D CT scans after ACL reconstruction. Level of Evidence: III, retrospective comparative study.